Usability Evaluation of Encyclopedia Websites (International Journal of Innovative Computing, 2021)
Usability is an important aspect that every website should focus more. It tells us how well and success website will function with real users. Many people often think usability tests are expensive and time-consuming. It can be a cost-effective and time saver with usability testing instead of spending more time fixing an unusable website. This study evaluates the usability of encyclopedia websites by using automated usability testing tools and questionnaire methods. The questionnaire was developed based on a standard form called Website Analysis and Measurement Inventory (WAMMI) that identified 20 common usability questions divided into five categories. Each category deals with one aspect of usability. Simultaneously, the automated usability testing tools used in this study were Pingdom and GT Metrix to calculate and analyse the website performance of selected encyclopedia websites based on website components including page load time, media size and overall web performance grades. This study could help web designer, developer, and practitioners design better and more user-friendly encyclopedia websites.
Keywords: Usability, testing, pingdom, GT metrix, load time, performance